2017
DOI: 10.1111/acer.13302
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Factors Associated with Lifetime Abstinence from Alcohol in the 1979 National Longitudinal Survey of Youth Cohort

Abstract: Background The choice and definition of a comparison group in alcohol-related health studies remains a prominent issue in alcohol epidemiology due to potential biases in the risk estimates. The most commonly used comparison group has been current abstainers, however, this includes former drinkers who may have quit drinking due to health problems. Lifetime abstention could be the best option but measurement issues, selection biases due to health and other risk factors, and small numbers in populations are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
(55 reference statements)
4
21
1
Order By: Relevance
“…Several studies have found a social gradient in non-drinking (Jefferis et al, 2007;Ng Fat and Shelton, 2012), with the more socially and economically disadvantaged being less likely to drink alcohol. In terms of health, Kerr et al's (2017) findings are consistent with a different prospective study in the UK, which found limiting longstanding illness from an early age and persistent limiting longstanding illness from childhood to be associated with lifetime abstention (Ng Fat et al, 2014). Since this relationship was found early on in life, it suggests that poor health may be causing lifetime abstention, rather than the reverse, as has been implicated in later-life in comparison with moderate drinkers.…”
Section: Commentary On Kerr Et Al (2017): More Evidence That Social Asupporting
confidence: 87%
See 4 more Smart Citations
“…Several studies have found a social gradient in non-drinking (Jefferis et al, 2007;Ng Fat and Shelton, 2012), with the more socially and economically disadvantaged being less likely to drink alcohol. In terms of health, Kerr et al's (2017) findings are consistent with a different prospective study in the UK, which found limiting longstanding illness from an early age and persistent limiting longstanding illness from childhood to be associated with lifetime abstention (Ng Fat et al, 2014). Since this relationship was found early on in life, it suggests that poor health may be causing lifetime abstention, rather than the reverse, as has been implicated in later-life in comparison with moderate drinkers.…”
Section: Commentary On Kerr Et Al (2017): More Evidence That Social Asupporting
confidence: 87%
“…Findings from Kerr et al (2017) (Kerr et al, 2017), add to the growing body of literature on lifetime abstention and abstention more generally. Several studies have found a social gradient in non-drinking (Jefferis et al, 2007;Ng Fat and Shelton, 2012), with the more socially and economically disadvantaged being less likely to drink alcohol.…”
Section: Commentary On Kerr Et Al (2017): More Evidence That Social Amentioning
confidence: 81%
See 3 more Smart Citations